Global interior eddy available potential energy diagnosed from Argo floats. Issue 5 (10th March 2014) - Roullet, Guillaume; Capet, Xavier; Maze, Guillaume
Abstract By combining all Argo profiles for the period 2002 to present, a cumulative density function is constructed on a 3‐D grid of the global ocean. This function quantifies the statistics of isopycnals: time‐averaged density, root‐mean square of isopycnal displacement, and eddy available potential energy (EAPE). EAPE is the analogue of the eddy kinetic energy, but for the potential energy reservoir. Because it is essentially tied to the spatial structure and magnitude of mesoscale activity, EAPE is an important quantity that should be useful to evaluate eddy resolving/permitting model turbulence and circulation. Among other striking features are the turbulent behavior of Pacific and southern Atlantic Tsuchiya jets and subsurface EAPE maxima in some parts of the ocean, particularly in the Southern Ocean.